Experimental investigation on performance of downhole electric heaters with continuous helical baffles used in oil shale in-situ pyrolysis. (25th January 2019) - Guo, Wei; Wang, Zhendong; Sun, Zhongjin; Sun, Youhong; Lü, Xiaoshu; Deng, Sunhua; Qu, Lili; Yuan, Wang; Li, Qiang
Highlights: The suitable heat transfer structure for downhole heat injection technology is obtained by simulations. The heat transfer and flow resistance characteristics of the four heaters are studied experimentally. The electric heater with 110 mm helical pitch has the best comprehensive performance. Heaters with smaller helical pitch values produce less irreversibility in the heat transfer process. Abstract: To rapidly produce oil, downhole heating technology requires an electric heater, which is limited by the diameter of the heat injection well, with long-term working stability and high-efficiency heat transfer. Simulations indicated that heater with continuous helical baffles is more suitable for downhole heating technology than heater with segmental baffles in terms of long-term working stability. Then, experiments were conducted on four continuous helical schemes with pitches of 50, 110, 160, and 210 mm. The test results showed that, in the test scope, the heater with the helical pitch of 110 mm (H110) had the best comprehensive performance, which was 2.95–3.75 times better than that of the heater with the helical pitch of 210 mm (H210). Under the same working conditions, heaters with smaller helical pitch values produce less irreversibility in the heat transfer process. In addition, the heaters with helical pitch values of 110, 160, and 210 mm were more effective at a lower Reynolds number, whereas the heater with the helical pitch of 50 mm could be used under a wide effective range of Reynolds numbers. The conclusions are benefit to setting the heating parameters of electric heater during the process of oil shale in-situ pyrolysis.